The correlation between hs C-reactive protein and left ventricular mass in obese women (Medical Journal of Indonesia, 2006)
Plasma C-reactive protein (CRP) concentrations are increased in obese individuals. In this study, we examined the correlation between hsCRP and left ventricular mass (LV mass). Fourty five healthy obese women and fourty five healthy non obese women as the controls group were studied by echocardiography and hsCRP. There was no significant correlation between hsCRP and left ventricular mass in obese women (r = 0.29, p 0.06). There was a significant correlation between hs CRP and body mass index (r = 0.46, p 0,002), and also hsCRP and visceral fat (r= 0.33, p 0.03). (Med J Indones 2006; 15:100-4)